Radiotherapy in the control of bleeding from primary and secondary lung tumours. (2nd April 2019) - Gaito, Simona; Hughes, Christopher; Woolf, David; Radhakrishna, Ganesh
Abstract : This literature review clarifies the role of radiotherapy in the management of low-volume haemoptysis. Embase and Medline were interrogated, and PRISMA guidelines were then used to select relevant articles. Seventy-eight articles were considered relevant and manually reviewed. The evidence suggests that external beam radiotherapy is more effective than endobronchial brachytherapy at controlling low-volume haemoptysis. There is no evidence to recommend a combination of the two techniques. Different doses and fractionations appear equally effective, with a potential survival advantage of higher dose regimens for fitter patients. Palliative radiotherapy is effective at controlling low-volume haemoptysis. External beam radiotherapy is the first-line treatment, with endobronchial brachytherapy recommended following external beam radiotherapy failure. Choice of dose and fractionation should take into account the patient's performance status.